Effect of different cultivation methods on strawberry’s antioxidant value - Lálity, Zs.; Borsos, É.; Ficzek, G.; Simon, G. (International Journal of Horticultural Science, 2018)
The small fruit and strawberry production is economically important in Serbian agriculture. The fresh fruit is sold in domestic markets, but the frozen and processed is mainly sold in foreign markets. The growers find themselves in an ever-expanding selection of the varieties, but besides the nursery and breeder’s descriptions of new cultivars, there are only few exact results for the biological and economical ability of the varieties, which makes easier to choose the proper cultivar. The performance of the varieties in modern strawberry production is worth to investigate by adaptive cultivation methods and production technique. In the case of new strawberry varieties we know neither their needs in production nor their real capability, so they have to be compared with an older, standard control variety (‘Clery’). The breeder’s manuals give only references for the needs of the production technique, of the variety, so it is necessary to have facts, which are based on objective testing results. In this work, a new variety (‘Joly’) is being compared with the control variety. Comparative study of individual varieties are required covering the antioxidant content of the fruits (FRAP) and variability of these amounts in different years of breeding as well as the production techniques under similar circumstances.